2017
DOI: 10.3892/ol.2017.6260
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis and detection of genetic mutations of pancreatic metastases: A report of four cases and review of the literature

Abstract: Abstract. The present study aimed to report our clinical experience regarding the diagnosis and detection of genetic mutations of pancreatic metastases, and to review the relevant literature to expand knowledge of this disease. A total of 4 cases involving pancreatic metastases, which were treated at The First Affiliated Hospital of Soochow University between January 2013 and July 2016, were retrospectively analyzed. This retrospective study considered the clinicopathological variables of the 4 patients, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Due to the scarcity of isPM, detailed systematic studies on the genetic/epigenetic profile of isPM have, to our best knowledge, not yet been presented. A MEDLINE (PubMed) based literature research thus revealed only one single presentation [222], reporting on two cases of pancreatic metastasis in RCC in which mutation analysis was performed, in order to evaluate the use of moleculary targeted therapies. There are, however, a few publications comparing non-metastatic with metastatic RCC, however these report on metastatic RCC as one group without taking into consideration different distant metastasis sites or the inclusion of pancreatic metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the scarcity of isPM, detailed systematic studies on the genetic/epigenetic profile of isPM have, to our best knowledge, not yet been presented. A MEDLINE (PubMed) based literature research thus revealed only one single presentation [222], reporting on two cases of pancreatic metastasis in RCC in which mutation analysis was performed, in order to evaluate the use of moleculary targeted therapies. There are, however, a few publications comparing non-metastatic with metastatic RCC, however these report on metastatic RCC as one group without taking into consideration different distant metastasis sites or the inclusion of pancreatic metastasis.…”
Section: Discussionmentioning
confidence: 99%